DEVELOPMENT OF TEACHING MATERIALS BASED ON PROJECT BASED LEARNING FOR EDITING COURSE - Reni Oktaviani (Esteem Journal of English Education Study Programme, 2024)
The aim of this study was to provide project-based learning-based teaching materials for editing courses. This study makes use of the ADDIE paradigm for research and development. Writing learning outcomes, questionnaires, and observation were utilized to collect research data. Expert and peer assessments provided the data for the analysis. The findings demonstrated that successful learning outcomes were achieved by developing project-based learning-based teaching materials for fourth-year Indonesian Language and Literature Education Study Program students in the Editing course. This helps students revise their writing more effectively, which enhances their writing abilities. Thus, the research's implications concern students' comprehension of modifying and creating instructional materials in order to meet learning objectives. This tactic has a big impact on learning.